Lixo eletrônico: um estudo sobre o tratamento dos resíduos de equipamentos eletroeletrônicos no município de Palmas – TO - Leal, Heleno Manduca Ayres (Universidade Federal do Tocantins, 2019)
Brazil’s economy has been growing and transforming itself, which increases the consumption of electronic equipment and gadgets from the Information Technology- It – area. A huge amount of the worldwide population has been joining the Global Society of Information and digital economy, getting significant benefits and opportunities offered by them. The rise of high- speed networks and faster services and applications have brought opportunities to many people in many areas, such as education, health care, government, entertainment and commerce. At the same time, the higher levels of available investments, the urbanization and industrialization in emergent countries are leading into an increasing number of electric and electronic equipaments, and consequently, to more electronic waste. The high consumption of these products brings us unwelcome consequences, when these gadgets stop being useful and start producing a huge amount of waste electrical and electronic equipment, or like is more known, electronic wastes. The subject addressed in this dissertation sought to show these residues have been treated by part of the population, the government, and what could be done with all the electronic waste produced that still has almost no treatment. This research hopes to show what are the actions taken by the public power, the management policies for the treatment of this kind of garbage, how much the actors involved know about electronic waste and also awareness through environmental education. The lack of an organized policy for gathering and discard of electronic waste contributes to environmental and health problems